The Mongols - Morgan, David (The peoples of Europe, 1998)
A revised edition of this highly praised introduction to the Mongol Empire. * Provides an overview of the government, religion, and politics of the Mongolian Empire. * Considers the effects of Mongol military campaigns on other countries and peoples in China, Russia, Persia and Europe